The Influence of Different Filters Substrate on Recirculation Systems to the Growth Rates of Selais Fish (Ompok hypopthalmus) - Nia Junaira Siambaton; Usman M Tang; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRAKThis research was conducted from April to Juni 2018, for 40 days in Technology Laboratory of Fisheries Faculty and Marine Sciences, University of Riau. The aim of the research was to know the best type of filter in reducing NH3 concentration and the effect of the water recirculation system on increasing growth and survival rates of Selais fish (Ompokhypopthalmus).used fish sized 5-8 cm. The method used was the experimental method with Completely Randomized Design (RAL) by using one factor of 5 treatments levels and 4 replications. The treatments were1)dacron, 2)bioball, 3) gravel, 4) charcoal, 5) zeolites. The conclusions obtained are use of Different Filter Substratesgive a real influence on growth and survival rate selais fish (Ompok hypopthalmus). The best result was treatment bioball with absolute growth weights (6,22 g), absolute growth length (4,50 cm), daily growth rate (3,81%) and survival rate (98,33%). Water quality parameters such as temperature 27,2-29,2 oC, pH 5,3-6,5, dissolved oxygen (DO) 4,3-5,5 mg/L, ammonia (NH3) 0,038mg/L, nitrite (NO2) 0,393 mg/L dan nitrate (NO3)0,683 mg/L.Keywords : Filter;Resirculation; growth; Survival Rate; Ompok hypopthalmus